The interpretation of Quranic texts through Khabar al-Wahid (solitary reports): Scope and limits according to legal theorists - Zahid Mehmood; Arslan Arif (Journal of Religion and Society, 2025)
This study explores the role of Khabar al-Wāḥid (solitary reports) in the interpretation (taʾwīl) of the Qur’ān, which is regarded as a qaṭʿī (definitive) source in Islamic law. While definitive texts hold a superior position over speculative evidence, instances of apparent conflict between the Qur’ān and khabar al-wāḥid have generated extensive scholarly debate. The primary objective of this research is to analyze the extent to which uṣūliyyūn acknowledged the authority of khabar al-wāḥid in Qur’ānic interpretation, particularly in three key areas: (1) abrogation of a Qur’ānic ruling through khabar al-wāḥid; (2) specification (takhsīs) of a Qur’ānic text through khabar al-wāḥid; and (3) addition to the Qur’ānic text, either through restriction (taqyīd) or the introduction of new rulings. The findings reveal that most scholars deny the possibility of abrogation of Qur’ānic rulings through khabar al-wāḥid after the Prophet’s ﷺ lifetime, though some allowed it during his life. Regarding specification, many jurists accepted the role of khabar al-wāḥid, while others restricted it due to its speculative nature. As for additions, scholars generally exercised caution, permitting them only in limited cases. Overall, the authority of khabar al-wāḥid in relation to the Qur’ān remains conditional and bounded by principles that safeguard the superiority of definitive evidence. The study recommends that Qur’ānic texts must always retain primacy, with khabar al-wāḥid applied only where it does not contradict the clear intent of the Qur’ān. Further, contemporary scholars should develop a unified methodological framework to minimize juristic conflicts, and this subject should be given greater emphasis in academic curricula to equip students with a balanced understanding of the relationship between definitive and speculative proofs. Keywords: Qur’ānic Interpretation, Khabar al-Wāḥid, Abrogation, Specification, Principles of Uṣūl al-Fiqh